In defense of fair value: Weighing the evidence on earnings management and asset securitizations - Barth, Mary; Taylor, Daniel (Journal of Accounting and Economics, 2010)
Dechow, Myers, and Shakespeare (DMS, 2009) find a negative relation between income from securitization activities and income from non-securitization activities. DMS interprets this finding as indicating that managers use the flexibility available in fair value accounting rules to smooth earnings. We clarify the role of fair value in accounting for asset securitizations, discuss alternative explanations for the evidence presented in DMS, and offer suggestions for future research. We caution against inferring the desirability of any particular accounting method from earnings management research.